PEMBERANTASAN TINDAK PIDANA KORUPSI INDONESIA DAN SINGAPURA - Nugroho, Cahyo Jati; Tan, Winsherly; Situmeang, Ampuan (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2024)
According to data from the anti-corruption education center released by Transparency International's Corruption Perceptions Index, Indonesia ranks 96th in 2021 in the corruption perception index with a score of 38 on a scale of 100. This study aims to determine the differences in the regulation and imposition of sanctions on perpetrators of corruption between Indonesia and Singapore. With Normative legal research, data is collected by literature study using secondary data which includes primary, secondary and tertiary legal materials which will be reviewed and studied one by one. This research provides results that show that there are several differences in preventing criminal acts of corruption in Indonesia and Singapore in terms of legislation, criminal sanctions, and anti-corruption institutions.